2017
DOI: 10.1016/j.clim.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced formation of giant cells in common variable immunodeficiency: Relation to granulomatous disease

Abstract: Peripheral monocytes from patients with common variable immunodeficiency (CVID) had on average a 2 fold greater tendency to form giant cells in medium without additional cytokines. Giant cell formation was faster and 3 to 5 fold higher in most CVID cells compared to normal. Addition of IL4, GMCSF, IFNγ, TNFa and both T cell and monocyte conditioned media promoted monocyte fusion of some CVID individuals over 5 fold the normal average level, with combinations of cytokines and monokines acting synergistically. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…A higher fusion index contributes to formation of granuloma (a lymphoproliferative complication) and is related to chronic inflammation (eg, inflammatory cytokines, particularly IFN-γ and TNF) and lymphocyte concentration. Of note, in vitro, the fusion rate of monocytes treated with immunoglobulin-based products can be increased, thus raising the debate of whether this standard treatment is involved in the risk of granulomatous disease, possibly by enhancing FcγRI expression [78].…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…A higher fusion index contributes to formation of granuloma (a lymphoproliferative complication) and is related to chronic inflammation (eg, inflammatory cytokines, particularly IFN-γ and TNF) and lymphocyte concentration. Of note, in vitro, the fusion rate of monocytes treated with immunoglobulin-based products can be increased, thus raising the debate of whether this standard treatment is involved in the risk of granulomatous disease, possibly by enhancing FcγRI expression [78].…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…Another cause that might underlie the development of CD in CVID patients is enhanced granulomas formation in CVID. An increased trend of monocytes forming giant cells has been demonstrated in CVID, which contributed to elevated granulocyte-macrophage colony-stimulating factor, IL−4, IFN-γ, and TNF-α [ 84 , 299 ]. Besides, Scott-Taylor et al reported a greater trend of CVID monocytes fusing in immunoglobulin-conditioned media, which suggest that standard immunoglobulin replacement therapy can contribute to granuloma formation [ 299 ].…”
Section: Inflammatory Bowel Disease In Common Variable Immunodefimentioning
confidence: 99%